MANFAAT KEGIATAAN OLAHRAGA BAGI PEMUDA SEHATKAN TUBUH, KUATKAN JIWA (BANNER) - Resman , Yuza; Firjatullah, Bagasnand; Al Ajwani, Rahmat; Muhammad Siregar, Fadel; Ferry Andrean Syahputra (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
Sports activities are not just physical activities, they also have a big positive impact on mental and emotional health. For young people, sport is one of the keys to keeping the body healthy and the soul strong. In this banner, the main benefits of sports activities for youth will be explained, including increasing physical fitness, controlling stress, increasing concentration, and character building. Let's explore together how through sport, youth can develop their potential holistically and have a positive impact on their lives and society as a whole. Keywords: Youth, Sports, Banner.